Teachers’ Pedagogical Competencies in Implementing Contextual Teaching and Learning in Vocational High Schools in South Sulawesi - Mustaqimah, Mustaqimah; Dollah, Syarifuddin; Basri, Muhammad; Asiza, Nur; Akib, Muhaiminah (International Journal of Language Education, 2025)
This study examines English teachers' abilities to implement pedagogical competence in teaching English for Specific Purposes (ESP) in vocational high schools. Using an interpretive qualitative case study approach, the study examined five teachers from two different vocational high schools, using semi-structured interviews, observations, and document analysis to collect data. The findings revealed three main themes: the ability to design contextual learning, using interactive learning methods, and implementing authentic assessments. Teachers demonstrated competence in integrating English with vocational competence, tailoring their teaching to meet the specific needs of students' future careers. They utilized task-based learning, collaborative group discussions, and technology-based media to engage students and enhance their learning experiences. In addition, teachers used practice-based assessments, such as simulations and project-based assignments, to ensure that students could apply their English skills in real-world scenarios. This study emphasizes the importance of pedagogical competence in fostering an effective ESP learning environment where students are prepared for the demands of their respective industries. The implications of this study suggest that improving teachers' pedagogical competence can significantly improve ESP teaching, providing students with relevant skills for success in their future professions. This research contributes to developing teacher training programs aimed at improving vocational education.